Biogeographic patterns of bacterial microdiversity in Arctic deep-sea sediments (HAUSGARTEN, Fram Strait) - Buttigieg, Pier Luigi; Ramette, Alban (Frontiers in Microbiology, 2015)
Marine bacteria colonising deep-sea sediments beneath the Arctic ocean, a rapidly changing ecosystem, have been shown to exhibit significant biogeographic patterns along transects spanning tens of kilometres and across water depths reaching several thousands of metres (Jacob et al., 2013). Jacob et al. adopted what has become a classical view of microbial diversity based on operational taxonomic units clustered at the 97% sequence identity level of the 16S rRNA gene and observed a very large microbial community replacement at the Hausgarten Long-Term Ecological Research station (Eastern Fram Strait). Here, we revisited these data using the oligotyping approach with the aims of obtaining new insights into ecological and biogeographic patterns associated with bacterial microdiversity in marine sediments and of assessing the level of concordance of these insights with previously obtained results. Variation in oligotype dispersal range, relative abundance, co-occurrence, and taxonomic identity were related to environmental parameters such as water depth, biomass, and sedimentary pigment concentration. This study assesses ecological implications of the new microdiversity-based technique using a well-characterised dataset of high relevance for global change biology.